THE EFFECT OF HAMBURGER STRATEGY TOWARDS STUDENTS’ WRITING SKILL IN RECOUNT TEXT AT THE FIRST GRADE OF MAN 4 KEDIRI - Jalil, Ahmad (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2020)
The aim of the research was to analyze whether Hamburger strategy was effective to be used in teaching writing recount text at the first grade of MAN 4 Kediri. This research was quantitative research approach, whereas the research design used was posttest-only control-design. This research used two classes which became experimental group (X MIA 2) and control group (X MIA 1). In experimental group was taught by using Hmaburger strategy, whereas control group was taught without Hamburger strategy. The instruments used in the research was written test. The procedure lasted 6 meetings and 1 meeting to do test. The result of t-test showed that: the mean score of experimental group (M = 74.1) was higher than control group (M = 69.12), and independent-samples t-test which values of the sig. 2-tailed was 0.3% or 0.003 and 0.003 < 0,05. Thus, it could be concluded that Hamburger strategy was effective in teaching and learning of English writing recount text. This result suggests that the writing aspects which the students significantly outperformed were content, organization, vocabulary, language use, and mechanics.